PENGARUH MEDIA PEMBELAJARAN VIDEO COMPACT DISC (VCD) TERHADAP HASIL BELAJAR SERVICE ATAS BOLAVOLI (STUDI PADA SISWA KELAS XI SMA MUHAMMADIYAH 1 BABAT LAMONGAN) - KHOIRU IHSAN, FATHONI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In the globalitation era the development of science and technology increase rapidly. That is very large until covers almost of human life aspect. The technology make us update and efforts in using technology product in teaching and learning. The teachers are reguired to be able to use technology tool, that provided by the school and its’n impossible that its tools suitable with the development and it can stimulate the their minds, feel and students willingness it can make learning process for the students. The purpose of this research are: (1) Influence of the use of VCD in volleyball overhand serve for 11th grade of Muhammadiyah 1 Senior High School Babat Lamongan. (2) How big ase the influence of VCD result in volleyball overhand serve for 11th grade of Muhammdiyah 1 Senior High School Babat Lamongan. The sample of this research students of 11th science 2 grade are 46 students as the experiment group and there are 36 students in 11th science 1 grade as the controlling group. This research use cluster random sampling technique from  170 students from five class in 11th  grade. The type of this research is experiment research with the descriptive quantitative approaching.  Based on the data analysis that has been done the result are the it use mann whitney u with significan 0,05, the result is mann whitney u 0,014 < significan 0,05, it means there is an not influence of significan by using Video Compact Disc (VCD) in volleyball overhand serve. The measure of influence has given by using VCD to the result of volleyball overhand serve is 7%.  There fore make a conclusion that there was an influence of significan by using VCD on the result of volleyball overhand serve in 11th grade of Muhammadiyah 1 Senior High School Babat Lamongan. Keywords: Video Compact Disc (VCD), Learning Result, Volleyball Overhand Serve.